PERANCANGAN SISTEM INFORMASI PENDATAAN WARGA SEKOLAH BERBASIS WEB PADA SDN 2 PAGELARAN - Puastuti, Dwi; ABB, Kurnia Ses (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2017)
Along with the growing of information and communication technology today, encouraging human activities to be more forward thinking in the use of technology. information technology plays an important role in supporting all human activities such as providing information services, especially in the field of education. One way to provide optimal information in the field of education is to build an official website that can be used the school and community to give each other and receive information quickly, accurately, and accurately. But the use of the website in the field of education has not been so equitable, as in SDN 2 Pagelaran where the state of his information service system is still manual, where the data processing students, teachers, and employees are still conventional, still using paper sheets and also Microsoft Exel so that data- data is easily lost or damaged. So there needs to be a system development of web-based information system to solve the problem. There are several stages in the development of this information system, namely the stage of analysis, system design, testing and implementation. This system is built using PHP and MySQL. With the information system is expected to be easy in the data processing of students, teachers and employees on SDN 2 Pagelaran and fix any shortcomings in the old system.Â